2007
DOI: 10.1111/j.1540-8167.2007.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of 8‐mm Gold‐Tip, Externally Irrigated‐Tip and 8‐mm Platinum‐Iridium Tip Catheters for Cavotricuspid Isthmus Ablation

Abstract: This study demonstrates equivalent efficacies of gold, platinum-iridium and externally Irr. tip catheters for successful de novo ablation of the CTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
2
21
3
1
Order By: Relevance
“…This closely agrees with our analytical estimate, which suggests a difference of between 21 and 28 Ω, according to the insertion depth of the active electrode. The difference in impedance found by Sacher et al [18] with 4-mm –irrigated– electrodes (116±12 Ω) and 8-mm electrodes (92±15 Ω) is also inside this estimated range (24 Ω).…”
Section: Estimate From Clinical Datasupporting
confidence: 59%
“…This closely agrees with our analytical estimate, which suggests a difference of between 21 and 28 Ω, according to the insertion depth of the active electrode. The difference in impedance found by Sacher et al [18] with 4-mm –irrigated– electrodes (116±12 Ω) and 8-mm electrodes (92±15 Ω) is also inside this estimated range (24 Ω).…”
Section: Estimate From Clinical Datasupporting
confidence: 59%
“…There are many potential reasons for this discrepancy, among them incorrect material properties, geometry of the myocardial surface, and differences in power application algorithm. However, the small increase in lesion dimensions we found in the simulations could explain the lack of significant difference in efficacy found in clinical trials that have compared the two electrode materials [9,10]. Therefore, while differences in electrode material properties may provide advantages in particular clinical situations, our modeling results suggest only potentially minor benefits.…”
Section: Discussioncontrasting
confidence: 45%
“…lesions with Au electrodes [7,8], clinical studies have not shown any significant differences in applied power, tip temperature, or clinical outcome between ablations with the two electrode materials [9,10].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations